Capacitive smoothing for solar PV system using small energy storage - Kok, Bing Qiang (2015)
Solar energy is intermittent by nature due to moving cloud transient and other meteorological factors and often requires battery for stabilization. The study focuses on the battery capacity and the power output of the solar PV system. Data analysis was performed on 6 months of solar data. Statistical techniques such as moving average and median filtering were applied to the result. Time characteristic from previous studies was used to obtain smaller battery capacity. Solar PV Ideal output was studied thoroughly to get better value. Results showed that statistical techniques did stabilize the power. However, battery capacity cannot be reduced further as it was insufficient to fill up the gap produced by the moving cloud transient. Hence, the capacity of 5 minutes was used in the simulation. Furthermore, the lowered ideal output did not help stabilize the power as the results show minor difference when compared with the higher ideal output.